Drug-induced vasculitis with multi-organ injury in a splenectomised patient and mycophenolate mofetil therapy – a case report - Pereska, Zhanina; Bekjarovski, Niko; Petkovska, Lidija; Simonovska, Natasha; Babulovska, Aleksandra; Naumoski, Kiril; Guchev, Filip (Институт за јавно здравје на Република Македонија = Institute of public health of Republic of Macedonia, 2025)
We present a case with p-ANCA positive general vasculitis and severe multi-organ injury in a splenectomised patient, which developed during ceftriaxone and metamizole administration for treatment of upper respiratory infection. Case report: A middle-aged woman with 400C fever and sore throat got a treatment with IV metamizole and ceftriaxone in a local hospital. She had a post- traumatic splenectomy 5 years ago. After metamizole, during ceftriaxone administration she felt burning in her face, developing red rush which spread over the face and darkened, later extended to her palms and feet. After visiting several clinics, she was referred finally to the University Clinic for Toxicology in Skopje. On admission, she had hypotension, hypoxemia, livid oro-pharynx, necrotic vasculitis with predominant facial distribution and unpalpable purpura on the extremities. The examinations revealed high levels of inflammatory biomarkers, anaemia, polyserositis, acute pancreatitis, hepatomegaly, acute kidney injury, disseminated intravascular coagulation, right eye vitreous haemorrhage and rhabdomyolysis. Microbiological investigations were negative. Immuno-serology showed positive p-ANCA. The acute renal failure and polyserositis resolved under methylprednisolone, meropenem, furosemide, low molecular weight heparin, fresh frozen plasma, and other symptomatic therapy, which decreased the inflammatory biomarkers, but DIC with thrombocytopenia persisted. A skin biopsy finding was inconclusive. After 25 days, the rheumatologist recommended mycophenolate mofetil with prednisolone peroral therapy during two years that resulted in stabilizing the vasculitis. The patient maintained stable after therapy discontinuation. Conclusions: Drug-induced vasculitis has the potential to induce a severe multi-organ injury with life-threatening complications. Mycophenolate mofetil procured a safe and successful treatment of drug-induced vasculitis. Splenectomy may be a potential risk factor for immunomodulated response to drugs and drugs interactions, especially during infections.
Keywords: drug induced vasculitis; multiorgan failure; ceftriaxone; metamizole; splenectomy; mycophenolate mofetil